Ética profesional de las secretarias y su incidencia en los procesos legales del decanato de la Facultad de Ciencias Sociales, Jurídicas y de la Educación de la Universidad Técnica de Babahoyo - Mora Bazantes, Sofia Irene (2020)
The present investigative work refers to the professional ethics of secretaries and their impact on the legal processes of the deanate of the faculty of legal, social and educational sciences, of the Technical University of Babahoyo. It could be perceived that not in all cases the importance of the use of good treatment, assertive communication, with ethical attitudes, among other factors that influence the successful development of the work they carry out is put into practice. From this reality arises as a research problem How does the professional ethics of secretaries affect the legal processes of the dean's deanate of the Faculty of Legal, Social and Educational Sciences of the Technical University of Babahoyo, province of Los Rivers? The drafting applied the bibliographic documentary analysis where different perspectives on the subject were compared and expanded; techniques for collecting data that were surveys conducted on secretaries and administrative staff.